Trust Me! I Can Read Building from Strengths in the High School English Classroom - Lamping, Sally; Blase, Dean Woodring (Language and Literacy (Paperba, 2012)
This innovative guide shows teachers how to transform high school English students into passionate readers with a trust-based approach that honors both student choice and teacher expertise. The authors begin with a series of reflective invitations to help teachers rediscover trust in themselves and in their students. The book offers methods for building confidence and critical skills through thematic book groups, the whole-class novel, and independent reading. As teachers work through each methods chapter, they will begin to create their own trust-based curriculum with the help of “Extend Your Thinking” sections. Classroom examples from urban, rural, and suburban contexts help teachers interweave trust-building methods (small reading communities, critically engaging lessons, student-led seminars, artistic response, drama, and dialogue) to create an English classroom that is once again a place of possibility and power.